Use Cases for Software Development Analytics: A Case Study - Rique, Thiago; Dantas, Emanuel; Perkusich, Mirko; Gorgônio, Kyller; Almeida, Hyggo; Perkusich, Angelo (Anais do Simpósio Brasileiro de Engenharia de Software (SBES); 2022: Anais do XXXVI Simpósio Brasileiro de Engenharia de Software, 2022)
Context Software engineering activities provide practitioners with large volumes of data that software analytics tools can use for many purposes, including defect prediction and effort estimation. However, the adoption of such tools depends on the information they provide and the real needs of practitioners. While existing research has focused on what developers need, the needs of managers are not well understood. Aims This study provides an in-depth analysis of the information needs of software practitioners from one organization that performs research, development, and innovation projects with industry partners. Understanding these practitioners’ needs enables the development of better analytics solutions to support managerial decision-making. Method We interviewed practitioners in leadership positions and analyzed the collected data using Grounded Theory coding techniques, i.e., open and selective coding. Results We identified 19 software analytics use cases and classified them into four dimensions: quality, people, project management, and knowledge management. We also elicited several indicators to meet the identified use cases and captured key aspects concerning the organization’s analytics scenario. Conclusions Although our results are particularly relevant to organizations similar to the one in which we conducted the study, they aim to serve as input for implementing new analytics solutions by practitioners and researchers in general.